Islamic Fintech Contracts and Regulation in Indonesia: Online Lending, Pay Later, and Sharia Cards - Zainul Alim; Luqmanul Hakim; Ali Abdullah (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
The rapid growth of financial technology (fintech) in Indonesia has accelerated the development of Islamic digital financial products, including sharia peer-to-peer (P2P) lending, sharia pay-later services, and sharia credit cards. However, studies examining their contractual structures and regulatory frameworks from the perspective of Islamic law remain limited. This study employs a qualitative-descriptive approach based on library research. Data were collected from DSN-MUI fatwas, regulations issued by the Financial Services Authority (OJK) and Bank Indonesia, and relevant academic literature. The data were analyzed using content analysis to examine the contracts (akad) and regulatory provisions governing Islamic fintech products in Indonesia. The findings reveal that Islamic P2P lending applies qardh, wakalah, and ijarah contracts, while sharia pay-later services generally utilize murabahah and ijarah muntahiyah bi al-tamlik. Sharia credit cards are based on a combination of kafalah, qardh, and ijarah. Unlike conventional pay-later systems that involve interest-based charges, sharia schemes employ transparent profit margins to avoid riba. Although DSN-MUI fatwas provide a fundamental basis for sharia compliance, regulatory supervision and sharia governance mechanisms require further strengthening. Therefore, stronger coordination among OJK, Bank Indonesia, and DSN-MUI is necessary to ensure compliance with Islamic legal principles and the objectives of maqashid al-shariah.